Candidate genes associated with color morphs of female-limited polymorphisms of the damselfly Ischnura senegalensis - Takahashi, Michihiko (Heredity (Edinb), 2018)
Many Odonata species exhibit female-limited polymorphisms, where one morph is similar to the conspecific male in body color and other traits (andromorph), whereas one or more other morphs differ from the male (gynomorphs). Here we investigated the differentially expressed transcripts (DETs) among males and two female morph groups (gynomorphs and andromorphs) using RNA-seq to identify candidate transcripts encoding female-limited polymorphisms in the damselfly Ischnura senegalensis. Seven DETs that had significantly different expression levels between males and gynomorphs, but not between males and andromorphs, were identified. The expression levels of four of these candidate genes, doublesex (dsx), black, ebony, and chaoptin (chp), were selected for further analysis using qRT-PCR. Sequence analysis of the dsx amplicons revealed that this gene produced at least three transcripts. Two short transcripts were mainly expressed in males and andromorphs, whereas the long transcript was specifically expressed in both morph female groups; that is, the expression pattern of the dsx splice variants in andromorphs was an intermediate between that of males and gynomorphs. Because the dsx gene functions as a transcription factor that regulates the sex-specific expression of multiple genes, its splice variants in I. senegalensis may explain why the andromorph is female but exhibits some masculinized traits. Because we did not detect different coding sequences of the candidate genes among the different morphs, a diallelic genomic region controlling alternative splicing of dsx, thus determining female-limited polymorphism in I. senegalensis most likely lies in a non-coding region of the dsx gene or in a gene upstream of it.